A PENERAPAN PENGEMBANGAN METODE PEMBELAJARAN PARTISIPATIF SEBAGAI UPAYA PENINGKATAN KETUNTASAN BELAJAR PADA PESERTA DIDIK KEJAR PAKET C PKBM BINTANG TUNAS MULIA KECAMATAN TANAH SAREAL KOTA BOGOR - Astuti, Dini Puji; Khairunnisa, Arin (Education For All, 2023)
The purpose of this study was to determine the application of participatory learning methods in improving learning completeness. The background of this research is that the method used is still using conventional learning methods. Where students are not fully involved in the learning process, so that the learning process is only fixated on one source and learning becomes one-way. Students cannot develop their potential, because they are not given the opportunity to be active during the learning process. This study aims to analyze the implementation process and the results of the development of participatory learning methods. This study uses a qualitative approach. The research location is PKBM Bintang Tunas Mulia, Tanah Sareal District, Bogor City. Data collection was carried out using interviews, observation, and documentation. The research subjects consisted of administrators, tutors, and Package C pursuit students. The validity of the data used triangulation of sources, methods and theories. Data analysis techniques use data collection, reduction, display, and verification. The findings from this study are in the initial activities, namely fostering familiarity, identifying needs and obstacles, preparing learning programs. In the learning process using participatory learning techniques, and participatory learning strategies / methods. The implementation of participatory learning methods is structured into opening, core and closing activities in the teaching and learning process. The stage used is in accordance with the theory of the implementation stage of the participatory learning method. The learning outcomes were in the form of increased learning completeness in PKBM Bintang Tunas Mulia Package C students.